THE EFFECT OF SEA SAND SUBSTITUTION ON THE PLASTIC LIMITS OF CLAY SOIL: A Literature Study of Soil Classification and CBR: PENGARUH SUBSTITUSI PASIR LAUT PADA BATAS PLASTIS TANAH LEMPUNG: Studi Literatur Terhadap Klasifikasi Tanah dan CBR - Kurniawan Ndruru, Fajar (LPPM UPMI, 2024)
This study aims to review the existing literature on the effect of sea sand substitution on the plastic limit of clay soil, as well as its impact on soil classification and California Bearing Ratio (CBR) values. Clay soils, which often have high plasticity, face various challenges in civil engineering applications, especially in terms of their stability and bearing capacity. The addition of sea sand, which is non-plastic, is expected to reduce the plasticity of clay soils and improve their performance in construction. Through a review of various literature studies, it was found that sea sand substitution generally decreases the plastic limit and plasticity index of clay soils, resulting in a change in soil classification from highly plastic to more granular soils. In addition, this decrease in plasticity also contributes to an increase in the CBR value, indicating an increase in the soil bearing capacity. However, the results of the review also emphasize the importance of determining the optimal proportion of sea sand to achieve a balance between improving mechanical properties and soil stability under different environmental conditions. Overall, this review concludes that sea sand substitution in clay soil can be an effective method to improve the bearing capacity and stability of the soil, but further research is needed to optimize its application in real construction projects.